Love can't feed you : a novel - Sy, Cherry Lou (Dutton, 2024)
"A beautiful, tender yet searing debut novel about intergenerational fractures and coming of age, following a young woman who immigrates to the United States from the Philippines and finds herself adrift between familial expectations and her own burning desires Love Can't Feed You is a stunning, heartbreaking, and compressed look at coming of age, shifting notions of home, and the disintegration of the American dream. It asks us: What does it mean to be of multiple cultures without a road map for how to belong? After a harrowing flight, Queenie, her younger brother, and their elderly Chinese father arrive in the United States from the Philippines. They're here to finally reunite with Queenie's Filipina mother, who has been working as a nurse in Brooklyn for the past few years-building a life that everyone hopes will set them up for better prospects. But her mother is not the same woman she was in the Philippines: Something in her face is different, almost hardened, and she seems so American already. Queenie, on the cusp of adulthood, has big dreams of attending college, of spending her days immersed in the pages of books. But there is not enough money for her and her brother to both be in school, so first she must work. Queenie rotates through jobs and settles, tentatively, into her new life, but her brother begins to withdraw and act out, and her father's anger swells. As the pressures of assimilation compound, and the fissures within her family deepen into fractures, Queenie is left suspended between two countries, two identities, and two parents"--